Materials for the 21st century - Segal, David (Oxford: Oxford University Press, 2017)
What does cotton candy, which dissolves at the touch, have in common with Kevlar, used for bullet-proof vests? How can our understanding of such materials help us to tackle essential problems of the 21st century? 0Materials play a key role in our search for solutions to many pressing issues. They underpin many industries, are critical for the development of consumer goods, are essential components of medical diagnostic techniques, offer hope for the treatment of currently incurable diseases, and provide answers to environmental problems. This handbook is a guide to the materials we rely on for the future. 0'Materials for the 21st Century' serves as a useful resource for undergraduate and high school students preparing for a career in physical sciences, life sciences,or engineering, by helping them to identify new areas of interest. It is also an excellent reference for readers interested in learning more about the diverse range of materials that underlie key aspects of our economy and everyday lives.
Includes bibliographical references and index.
Keywords: Materials